2001
DOI: 10.1086/324568
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation in Juvenile Red Kangaroos (Macropus rufus) after Pouch Exit: Higher Metabolism and Evaporative Water Requirements

Abstract: , T. J. (2001). Thermoregulation in juvenile red kangaroos (Macropus rufus) after pouch exit: higher metabolism and evaporative water requirements. Physiological and Biochemical Zoology, 74 (6), 917-927. Thermoregulation in juvenile red kangaroos (Macropus rufus) after pouch exit: higher metabolism and evaporative water requirements AbstractThe population dynamics of red kangaroos (Macropus rufus) in the Australian arid zone is tightly linked with environmental factors, which partly operate via the survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Evaporative water loss (EWL) -the rate of water loss from the body due to evaporation -is an important variable related to the resistance to dehydration in vertebrates, which in small endotherms could be of crucial relevance to survival (Anderson et al, 1997;Hayes et al, 1998;Maloney and Dawson, 1998;Munn and Dawson, 2001;Wang and Wang, 2000;Williams and Tieleman, 2000). The repeatability of this trait was studied by Hayes and colleagues (Hayes et al, 1998; see also Hayes and Jenkins, 1997), who found up to 65% repeatable variation.…”
Section: Introductionmentioning
confidence: 99%
“…Evaporative water loss (EWL) -the rate of water loss from the body due to evaporation -is an important variable related to the resistance to dehydration in vertebrates, which in small endotherms could be of crucial relevance to survival (Anderson et al, 1997;Hayes et al, 1998;Maloney and Dawson, 1998;Munn and Dawson, 2001;Wang and Wang, 2000;Williams and Tieleman, 2000). The repeatability of this trait was studied by Hayes and colleagues (Hayes et al, 1998; see also Hayes and Jenkins, 1997), who found up to 65% repeatable variation.…”
Section: Introductionmentioning
confidence: 99%
“…At this 'in-out' stage, the young kangaroo is still unable to maintain deep body temperature (T b ) for long periods, regularly returning to the pouch for warmth and safety Dawson, 1995). By 230-250·d, thermoregulation is well developed (Munn and Dawson, 2001) and the young kangaroo permanently leaves the pouch, becoming a young-at-foot (YAF; mass 4-5·kg). YAF red kangaroos forage in association with their mothers but also continue to take milk by putting their head into the pouch to access the same teat used during pouch-life.…”
Section: Introductionmentioning
confidence: 99%
“…It is not for another 100·days or so that the YAF is fully weaned, at around 360·d and weighing 10-11·kg Dawson, 1995). Once young kangaroos have permanently left the mother's pouch they face the same environmental challenges as adults, but their smaller body size and high-energy requirements for growth (Munn and Dawson, 2001;Munn and Dawson, 2003) potentially impact on their ability to meet such thermal challenges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations